Rehabilitation of Urban Parks with Recycling of Construction and Demolition Waste in Mexico City - Quintero-Navarro, Hugo Alberto; Rojas-Valencia, María Neftalí; Martínez-Cruz , Alfredo (New Environmentally-Friendly Materials, 2025)
Mexico City has experienced a rapid urbanization process, which has led to a socio-environmental crisis characterized by the generation of construction and demolition waste (CDW). The generation of CDW has been favored by the growth of the construction industry, the decrease in the useful life of buildings and an increase in the number of new buildings. To reduce the environmental impacts of CDW, recycling initiatives have been developed, offering alternatives for sustainable urban development. This study examines the use of recycled materials from CDW for urban park rehabilitation, focusing on the production of sustainable urban furniture. CDW as recycled material can be useful because it reduces the need for new resources, preserves land for future urbanization, protects the environment, and reduces transportation costs and energy needs A bibliographic analysis explored urban growth trends, CDW management methods, and the benefits of urban green spaces. As part of the project, urban furniture such as benches and planters was manufactured using recycled aggregates from CDW. The results demonstrate the functionality and sustainability of these elements, while providing recommendations on optimal aggregate sizes and compaction techniques. The urban furniture built using CDW (to manufacture benches, planters, jogging tracks and gabions), turned out to be totally functional, meeting the expectations of use This approach represents a viable alternative to natural fine aggregates, contributing to sustainable city development.